The effect of previous arthroscopic surgery on total knee arthroplasty outcomes and complication rates - Karaali, Evren; Ciloglu, Osman (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the effect of previous arthroscopic surgery on total knee arthroplasty outcomes and complication rates.Material and Methods: This retrospective study included patients who underwent total knee arthroplasty due to grade 4 osteoarthritis, according to the Kellgren-Lawrance classification system in a tertiary hospital, between January 2012 and December 2016. The patients were divided into two groups according to whether or not they had undergone previous knee arthroscopy. The arthroscopic procedure included degenerative meniscus tear subtotal excision and synovectomy. The data of the two groups were compared. Outcome measures were the visual analog scale, McMaster Universities Osteoarthritis Index, Knee Society scoring system and knee range of motion.Results: The previous arthroscopy-free group comprised 94 patients (35 males, 59 females), and the previous undergoing arthroscopy group included 73 patients (23 males, 50 females). The mean age of previous arthroscopy-free group was 63.12 ± 2.8 years (range, 57 to 68), and the mean age of previous undergoing arthroscopy group was 62.42 ± 3.9 years (range, 55 to 73). The groups were similar in terms of age, gender, body mass index, follow-up periods, sides, and complications (p > 0.05 for all). In assessments at the end of 4 years, the groups were similar in respect of visual analog scale, McMaster Universities Osteoarthritis Index, Knee Society scoring system and knee range of motion. Conclusions: The results of this study showed that clinical outcomes and complications were similar in patients with primary total knee arthroplasty and no previous procedure and those who had previously undergone knee arthroscopy. In the light of these preliminary results, previous knee arthroscopy has no negative effect on the outcomes of total knee arthroplasty and complication rates.